The prospect on accuracy and universality of the river ecology environmental assessment method in IFIM - Imai, Takashi; Sekine, Masahiko; Ukita, Masao; Yang, Jidong; Kawamoto, Yasuo (ENVIRONMENTAL SYSTEMS RESEARCH, 1998)
Recently, the purposes of river improvement works have became not only the protection for flood but also the improvement of ecosystem quality. In this context, habitat evaluation procedures are becoming important. The Instream Flow Incremental Methodology (IFIM) is one of the most popular habitat evaluation method, but still there is little application experience in Japan. In this paper, we study the accuracy and applicability of fish habitat evaluation method by IFIM. At first, we surveyed habitat variables, such as velocity, depth, substrate and cover, to derive suitability-of-use curves, which are the core technique in IFIM, during the summer and the autumn in 1997 in the Furukou River, Yamaguchi prefecture. Then, we compare the observed fish distribution with calculated habitat distribution by using the suitabilityof-use curves obtained from the same river, which showed a good accordance. Next, we compare the observed fish distribution with calculated habitat distribution by using the suitability-of-use curves obtained from literature, which showed a bad accordance. Those results imply that the suitabilityof-use curves obtained from a river will show a good accordance when it is used in the same river, but cannot apply to other rivers.